THE EFFECT OF FINANCIAL LITERATION ON FINANCIAL PERFORMANCE IN COOPERATIVES OF STATE EMPLOYEES IN BANDAR LAMPUNG: FINANCIAL MANAGEMENT BEHAVIOR OF COOPERATIVE MANAGERS AS INTERVENING VARIABLES - Liya Ermawati (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2019)
Allegedly, the reason for the number of cooperatives not actively running cooperative units is because there are still many financial problems. Individual needs and increasingly complex financial products require cooperative managers to have adequate financial literacy. Individuals need basic financial knowledge and the ability to effectively manage financial resources for better welfare and development of cooperatives.A person's ability to use money depends very much on the knowledge they have, the better the financial literacy that someone has, the better the financial management behavior of that person. This kind of thing, then, will have an impact on one's financial performance. Therefore, studies regarding this matter are very important to do. In this study, the total sample was 50. all the data obtained were analyzed using path analysis. Path analysis is used to analyze the pattern of relationships between variables in order to determine the direct and indirect effects of a set of independent variables on the dependent variable Based on the results of data processing, it can be seen that the value of the direct effect of the variable behavior of financial management on financial performance is equal to 0.681. Whereas, the indirect effect of variables x1, x2 and x3 on financial performance through financial management behavior is 0.0051 (0.367 x 0.480 x 0.029). by comparing the two values, it can be proved that the influence of knowledge variables (X1), understanding (X2), and application (X3) on financial performance is directly smaller than their influence on financial performance (Z) through financial management behavior (Y), so it can be concluded that the behavior of financial management is an intervening factor for financial literacy with financial performance Someone who has good financial literacy, coupled with proper financial management behavior, can be said as prosperous in terms of finances. By having good skills in managing finances, a cooperative manager will be free from financial problems so that the cooperative's financial performance will be achieved optimally.